Intranasal delivery of cancer-targeting doxorubicin-loaded PLGA nanoparticles arrests glioblastoma growth - Chung, Kunho; Ullah, Irfan; Kim, Nahyeon; Lim, Jaeyeoung; Shin, Jungah; Lee, Sangah C.; Jeon, Sangmin; Kim, Sun Hwa; Kumar, Priti; Lee, Sang-Kyung (TAYLOR & FRANCIS LTD, 2020)
Glioblastoma multiforme (GBM) is the most aggressive form of brain tumour and treatment is very challenging. Despite the recent advances in drug delivery systems, various approaches that allow sufficient deposition of anti-cancer drugs within the brain remain unsuccessful due to limited drug delivery throughout the brain. In this study, we utilised an intranasal (IN) approach to allow delivery of anti-cancer drug, encapsulated in PLGA nanoparticles (NPs). PLGA NPs were modified with the RGD ligand to enable A(v)beta(3)expressing tumour-specific delivery. IN delivery of RGD-conjugated-doxorubicin (DOX)-loaded-PLGA-nanoparticles (RGD-DOX-NP) showed cancer-specific delivery of NP and inhibition of brain tumour growth compared to the free-DOX or non-modified DOX-NP in the C6-implanted GBM model. Further, IN treatment with RGD-DOX-NP induces apoptosis in the tumour region without affecting normal brain cells. Our study provides therapeutic evidence to treat GBM using a non-invasive IN approach, which may further be translated to other brain-associated diseases.
Keywords: CENTRAL-NERVOUS-SYSTEM; CELL-CYCLE ARREST; DRUG-DELIVERY; BREAST-CANCER; BRAIN-TUMOR; RGD; EXPRESSION; LIPOSOME; PHARMACOKINETICS; CHEMOTHERAPY